Addressing Driver of Deforestation and Forest Degradation in Mizoram through Sub-National REDD+ Action Plan - Bhattarai, Nabin; Verma, Nemit; Rawat, R.S; Karky, Bhaskar Singh; Rawat, VRS (Journal of Forest and Livelihood, 2018)
Knowledge and understanding on drivers of deforestation and forest degradation (D&D) plays a vital role in development of policies and measures in countries moving ahead with REDD+ (Reducing Emissions from Deforestation and Forest Degradation) implementation at national as well as sub national level. The conference of Parties (COP) 15 also inspires the non-annex countries to identify drivers of D&D and means to address them in addition to stabilisation of forest carbon stocks. A National REDD+ Strategy (NS) or National REDD+ Action Plan (AP) is mandatory under the United Nations Framework Convention on Climate Change (UNFCCC) for any country wishing to receive international funding under the REDD+ payment. Forest ecosystems and drivers of D&D vary across countries and regions (within individual countries) and this type of plan which are developed at sub-national level in consultation with local stakeholders will support in REDD+ readiness as well as implementation at the local level. In addition, addressing drivers of D&D following this sort of process plays a bridging role between the local and national level for the implementation of REDD+ activities. This study primarily identifies the drivers of D&D in Mizoram State of India. Methods for this research were adopted from “Developing Sub-National REDD+ Action Plans: A Manual for Facilitators” published by the International Center for Integrated Mountain Development (ICIMOD) in 2017”. It was observed that, shifting cultivation is the main driver of D&D in the study area. To address the main driver, settled cultivation or permanent cultivation supported by horticulture crops should be adopted for better livelihood options.